Using blended and online learning to increase appreciation of learning outcomes: case of a problematic game design unit - Awidi, Isaiah T.; Harper, Tauel; Savat, David (Frontiers in Education, 2025)
IntroductionA key challenge for many academics is designing learning activities that are constructively aligned and effectively enhance students’ appreciation of their learning outcomes. This study investigates the impact of integrating active and blended learning strategies into a game design unit that had historically suffered from low student engagement and poor alignment with unit outcomes.MethodsTo address this issue, we introduced a series of active and blended learning activities, including an interactive design project, group work, the use of an online peer assessment tool, and online assessments requiring independent critical reflection and feedback on students’ learning experiences. A mixed-methods approach was employed. An online survey was administered via the LMS to 137 enrolled students, with 101 responses collected over a four-week period. Quantitative data were analyzed using ANOVA and linear multivariate analysis to assess the impact of these interventions.Results and discussionThe findings suggest that the introduction of active and blended learning strategies—particularly those that increased student participation in lectures and group discussions—enhanced overall engagement and improved student satisfaction with the unit. Students appreciated the availability of online tools and resources; however, online engagement alone did not consistently lead to improved learning experiences. The data indicated that the effectiveness of online learning was significantly influenced by the presence of consistent and clear feedback.ConclusionActive and blended learning strategies, when supported by thoughtful learning design and timely feedback, are effective in engaging students with their learning outcomes and enhancing the overall student experience. These findings underscore the importance of integrating interactive and reflective components into course design to foster deeper student engagement.